Seeking More Sustainable Merger and Acquisition Growth Strategies: A Spatial Analysis of U.S. Hospital Network Dispersion and Customer Satisfaction - William Ritchie; Ali Shahzad; Scott R. Gallagher; Wolfgang Hall (Geomatics, 2025)
The pursuit of mergers and acquisitions (M&A) is often an acclaimed strategy for firm growth, resource sharing, and extended reach into new market segments. However, in the healthcare marketplace, there are two very different perspectives related to M&A. On the one hand, the American Hospital Association commends M&A activity as a tool to reduce healthcare costs, drive quality, and serve rural markets. On the other hand, a recent United States’ Presidential executive order suggests that M&A in the healthcare space is harmful to healthcare due to its restrictions on competition and adverse impacts on patients. These conflicting perspectives reflect differing M&A views in mainstream management research, as well. The purpose of the current study is twofold. First, we aim to explore these two seemingly paradoxical perspectives by examining the degree of hospital network geographic dispersion that results from M&A activity. Second, we contribute to the broader M&A literature by drawing attention to the importance of considering geographic influences on M&A performance. Using a spatial analysis of 147 nationwide hospital networks comprising 1713 hospitals, we propose and find support for the notion that the degree of network dispersion, as measured by actual driving distances in healthcare networks, are correlated with patient experiences. Using ordinary least squares (OLS) regression to examine relationships between patient experiences and overall hospital network geographic dispersion, we found support for the hypothesis that more spatially dispersed healthcare networks are associated with lower overall performance outcomes, as measured by customer (patient) satisfaction. The implications of these findings suggest that growth strategies that involve M&A activity should carefully consider the spatial influences on M&A entity selection. Our exploratory findings also provide a foundation for future research to bridge the gap between industry and governmental perspectives on healthcare M&A practices.